2016
DOI: 10.1017/jog.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

The response of glaciers to climatic persistence

Abstract: ABSTRACT. The attribution of past glacier length fluctuations to changes in climate requires characterizing glacier mass-balance variability. Observational records, which are relatively short, are consistent with random fluctuations uncorrelated in time, plus an anthropogenic trend. However, longer records of other climate variables suggest that, in fact, there is a degree of temporal persistence associated with internal (i.e. unforced) climate variability, and that it varies with location and climate. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 53 publications
5
29
0
Order By: Relevance
“…The effects of persistence are dramatic: for both S or Ω forcing, 4 yr AR-1 persistence more than doubles σ L compared to length fluctuations driven by white forcing, and both 20 yr AR-1 and power-law persistence cause a ∼5-to-6-fold increase in σ L . This is consistent with the approximate proportionality between σ 2 L and τ AR1 predicted by theory (see, e.g., Roe and Baker, 2016;Robel et al, 2019). The power spectra of the forcings and responses show why persistence has such a strong effect.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The effects of persistence are dramatic: for both S or Ω forcing, 4 yr AR-1 persistence more than doubles σ L compared to length fluctuations driven by white forcing, and both 20 yr AR-1 and power-law persistence cause a ∼5-to-6-fold increase in σ L . This is consistent with the approximate proportionality between σ 2 L and τ AR1 predicted by theory (see, e.g., Roe and Baker, 2016;Robel et al, 2019). The power spectra of the forcings and responses show why persistence has such a strong effect.…”
supporting
confidence: 89%
“…While the comparisons above show that interior and terminus forcing elicit 275 different glacier responses due to the distinct geometries of the respective flux anomalies, we must also consider the possibility of climatic persistence in order to fully characterize an outlet glacier's response to natural climate variability. Roe and Baker (2016) showed that persistence in surface mass balance variability amplified the length fluctuations of mountain glaciers; we can expect similar principles to be especially relevant to outlet glaciers if they are sensitive to decade-scale ocean variability.…”
Section: Persistence In Variability 270mentioning
confidence: 84%
See 1 more Smart Citation
“…Though we have assumed that the noise forcing of ice shelf length includes no persistence in time (white noise), it would be more realistic to simulate ice shelf calving with autocorrelation in time. This would lead to greater stochastic glacier variability (Mantelli et al, ; Roe & Baker, ) and perhaps an even larger shift in the time‐averaged glacier state.…”
Section: Nonlinearity Of Noisy Processes Causes Grounding Line Retreatmentioning
confidence: 99%
“…1d,f). Therefore, although power-law behavior can be used to derive expected return times for extreme events (e.g., Roe and Baker 2016;Ault et al 2013b), the apparent negative scaling in the tropics should not be used to calculate return times for extreme events owing to the lack of negative power-law scaling behavior in this region. We refer to a given time series as ''white'' if it roughly had equal variance at all frequencies and had a flat slope (between 20.2 and 0.2) (Ault et al 2013b) in log-log space, such as precipitation over the North Atlantic in CESM (Fig.…”
Section: B Power Spectra Estimationmentioning
confidence: 99%